Kooperirovannye issledovaniia v stranakh SEV po khimioluchevomu lecheniiu bol'nykh rakom legkogo - Kiseleva, E S; Pitskhelauri, V G; Trakhtenberg, A Kh; Bidiak, I P; Zholkiver, K I (Medicinskaja radiologija, 1984)
The paper is concerned with a comparative analysis of the immediate and short-term results of chemo- and radiotherapy of 174 patients with well differentiated inoperable lung cancer. The data were presented by the participants of the CMEA cooperative trial (the Hungarian People's Republic, the USSR and the Czechoslovak Socialist Republic over the period of 1976-1980). In the course of a randomized study radiotherapy (at a summary dose of 60 Gy) was given to 98 patients, chemotherapy to 76 (methotrexate and 5-fluorouracil). Comparative analysis has shown that the use of adjuvant chemotherapy tends to improve an immediate therapeutic effect. In well differentiated squamous cell carcinoma, a marked positive effect was obtained in 48.6% of the patients as compared to 31.2% in radiotherapy alone. However, judging by the survival rates such differences in favor of chemotherapy were not revealed. After conservative treatment (radio- and chemotherapy) of patients with differentiated lung cancer in the inoperable stage 55.7% survived for 1, 17.27% for 5, 8.55% for 3 yrs. Direct correlation between the immediate effect of radio- and chemotherapy and the survival of the patients was revealed. Of 67 patients with a marked immediate effect 49 (73.1%) lived over 1 year, 8 out of 9 patients lived for 3 yrs.
Keywords: dospělí; klinické zkoušky jako téma; Carcinoma, Squamous Cell; Clinical Trials as Topic; Female; kombinovaná terapie; Fluorouracil; Adult; ženské pohlaví; Multi-Institutional Systems; USSR; Československo; nádory plic; lidé; Carcinoma; Antineoplastic Combined Chemotherapy Protocols; multiinstitucionální systémy; karcinom; protokoly protinádorové kombinované chemoterapie; Methotrexate; Adenocarcinoma; Male; fluoruracil; Aged; methotrexát; spinocelulární karcinom; Combined Modality Therapy; adenokarcinom; Lung Neoplasms; Hungary; lidé středního věku; Random Allocation; senioři; mužské pohlaví; SSSR; Maďarsko; Czechoslovakia; Middle Aged; náhodné rozdělení; Humans